ECO-INNOVATION PRACTICES AND BUSINESS PROCESSES IN FURNITURE SUPPLY CHAIN MANAGEMENT:: ANALYSIS MODEL PROPOSITION - Troccoli Marques da Silva, Natalia; Aparecida Santini Pigatto, Giuliana; Guilherme Satolo, Eduardo (Brazilian Journal of Management and Innovation (Revista Brasileira de Gestão e Inovação), 2023)
The Brazilian furniture industry is responsible for promoting a significant part of the economy. The still traditional production process and its main raw material, wood, require the use of various natural resources and, together with the other materials necessary for the elaboration of products, the sector produces a significant amount of waste. These situations require adequate procedures to reduce damage to the environment. Due to the need to adapt companies to a model that is less harmful to the environment, the study aims to analyze the relationship between eco-innovation practices and business processes in the management of the furniture supply chain, for the purpose of elaborating of an analysis model. By means of the concepts of furniture supply chain management and eco-innovation, a model was developed to analyze the relationships between them. The literature search of the sector and systematic literature review were used as a method. It was identified that the business processes susceptible to the application of eco-innovation practices to the management of the furniture supply chain. It was concluded that eco-innovation practices are related to the business processes customer relationship management, manufacturing management, supplier relationship management, product development and commercialization and return management, and these practices can be applied to the obtaining environmental benefits, contributing to a better understanding of the applicability of eco-innovation in the furniture industry.